2010
DOI: 10.1080/17470210903076826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of executive control in the Implicit Association Test: Why flexible people have small IAT effects

Abstract: The goal of the present research was to investigate the role of three central-executive functions-switching of mental sets, inhibition of prepotent responses, and simultaneous storage and processing (i.e., working-memory capacity)-in accounting for method variance in the Implicit Association Test (IAT). In two studies, several IATs with unrelated contents were administered along with a battery of central-executive tasks, with multiple tasks tapping each of the above executive functions. Method variance was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(182 citation statements)
references
References 37 publications
12
164
0
1
Order By: Relevance
“…The Quad model does not provide an exhaustive account of IAT performance, which is certainly influenced by processes that are not included in the model, including recoding (e.g., Chang & Mitchell, 2011;De Houwer et al, 2005;Kinoshita & Peek-O'Leary, 2005, 2006Meissner & Rothermund, 2013;Rothermund et al, 2009;Rothermund & Wentura, 2001, 2004Rothermund et al, 2005), task-set shifts and task-set simplification (e.g., Mierke & Klauer, 2001Klauer et al, 2010), and speed-accuracy tradeoffs (e.g., Brendl et al, 2001;Klauer et al, 2007). Klauer and colleagues have already demonstrated method variance in IAT performance related to task switching ability Mierke & Klauer, 2001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quad model does not provide an exhaustive account of IAT performance, which is certainly influenced by processes that are not included in the model, including recoding (e.g., Chang & Mitchell, 2011;De Houwer et al, 2005;Kinoshita & Peek-O'Leary, 2005, 2006Meissner & Rothermund, 2013;Rothermund et al, 2009;Rothermund & Wentura, 2001, 2004Rothermund et al, 2005), task-set shifts and task-set simplification (e.g., Mierke & Klauer, 2001Klauer et al, 2010), and speed-accuracy tradeoffs (e.g., Brendl et al, 2001;Klauer et al, 2007). Klauer and colleagues have already demonstrated method variance in IAT performance related to task switching ability Mierke & Klauer, 2001.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware of very little research that directly investigates the attitude-specific versus non-attitudinal nature of the processes that contribute to evaluative responses on implicit measures of attitude (but see Klauer et al, 2010;Mierke & Klauer, 2001. The purpose of the current research was to directly examine this question in the context of IAT performance.…”
mentioning
confidence: 99%
“…The executive function of switching is less strongly related to updating and inhibition (e.g., Klauer et al, 2010;Miyake et al, 2000) suggesting that WM span may not predict switch costs between bilinguals and monolinguals. Indeed, some studies have reported a bilingual advantage in switching (e.g., Prior & Gollan, 2011;Prior & Macwhinney, 2009), although even this effect has not been consistent (e.g., Hernández et al, 2013;Paap & Greenberg, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Building on this model, Friedman, Miyake, Young, DeFries, Corley, and Hewitt (2008) showed that "inhibition" correlates almost perfectly with "general executive function" and strongly correlates with "updating." Similarly, other studies have reported a strong relationship between inhibition ability and WM span (e.g., Klauer, Schmitz, Teige-Mocigemba, & Voss, 2010;Unsworth & Spillers;2010). Given this strong relationship, if bilinguals have an inhibitory control advantage, a similar advantage should be observed on WM tasks.…”
Section: Bilingual Working Memorymentioning
confidence: 99%
“…No such relationship appeared with respect to self-reported bias, suggesting that the effect is rooted in an automatic association between anger and social categories. An advantage of this task was its suitability for young children, for whom lengthy reaction time measures may not be appropriate (Ratcliff, Love, Thompson, & Opfer, 2012), especially measures like the IAT which centrally implicate executive function capacities (such as task switching; Klauer, Schmitz, Teige-Mocigemba, & Voss, 2010) that are notoriously unstable developmentally (e.g. Davidson, Amso, Anderson, & Diamond, 2006).…”
Section: Signatures Of Implicit Intergroup Attitudesmentioning
confidence: 99%